2013
DOI: 10.1111/liv.12312
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D is associated with increased whole body fat mass and greater severity of non‐alcoholic fatty liver disease

Abstract: Background Hypovitaminosis D is common in obesity and insulin resistant states. Increased fat mass in patients with non-alcoholic fatty liver disease (NAFLD) may contribute to hypovitaminosis D. Aims To determine the relation between plasma vitamin D concentration, severity of disease and body composition in NAFLD. Methods Plasma vitamin D concentration was quantified in 148 consecutive biopsy proven patients with NAFLD (non alcoholic steatohepatitis-NASH: n=81; and hepatic steatosis n=67) and healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 59 publications
9
94
1
2
Order By: Relevance
“…25 No 2: 175-181 peroxisome proliferator-activated receptor gamma (PPAR-γ) [12,13]. Although not all [14,15], many observational studies report associations between vitamin D deficiency and hepatic steatosis [12,16], the aggregate effect of which has been illustrated in a meta-analysis [17] confirming the presence of decreased serum 25-hydroxyvitamin D concentrations in such patients. Specifically, they were 26% more likely than healthy controls to be vitamin D deficient.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…25 No 2: 175-181 peroxisome proliferator-activated receptor gamma (PPAR-γ) [12,13]. Although not all [14,15], many observational studies report associations between vitamin D deficiency and hepatic steatosis [12,16], the aggregate effect of which has been illustrated in a meta-analysis [17] confirming the presence of decreased serum 25-hydroxyvitamin D concentrations in such patients. Specifically, they were 26% more likely than healthy controls to be vitamin D deficient.…”
Section: Introductionmentioning
confidence: 74%
“…Some studies have also inversely correlated serum 25-hydroxyvitamin D concentrations with elevated body fat, which is often seen in patients with comorbid hepatic steatosis [16,20]. Indeed adipose tissue has been reported to sequester vitamin D and reduce its bioavailbility, thus exacerbating suboptimum vitamin D status [21].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, when the studies are grouped for general comparison according to NAFLD diagnosis method or study population, some consistency is found. For example, the two studies using biopsy-based NAFLD diagnosis (from Italy and the USA) found a significantly lower serum vitamin D level in NAFLD patients and demonstrated a close association of vitamin D levels with both fibrosis and hepatocyte ballooning [8,18] . Furthermore, in two studies using B-mode ultrasound NAFLD diagnosis (again from Italy and the USA), serum vitamin D was also found to be an independent predictor of NAFLD [19,20] .…”
Section: Discussionmentioning
confidence: 99%
“…One of the most discussed mechanisms is explained by low bioavailability of vitamin D when high content of body fat acts as a reservoir for lipid soluble vitamin D and increases its sequestration (Wortsman et al, 2000). Furthermore, the synthesis of 25-OH D may be decreased in obese subjects because of hepatic steatosis (Targher et al, 2007;Dasarathy et al, 2014). In addition, low sun exposure and limited cutaneous vitamin D synthesis in obese patients may also play a role (Florez et al, 2007).…”
Section: Hypovitaminosis D and Body Composition Indicesmentioning
confidence: 99%